TARBIYATUL QULUB MELALUI DZIKIR - Haromaini, Ahmad; Rachman, Abdul; Al-Fahmi, Faiz Fikri (Islamika : Jurnal Agama, Pendidikan dan Sosial Budaya, 2021)
Abstract Humans were created with a clear mission. According to the expert commentators, there are three missions carried out by humans as Allah Almighty's creatures on earth, the mission of worshiping, the caliph, playing a role in prospering the earth. Then he was given some potential. One of these potentials is the heart "qalb". In several verses of the al-Qur'an, it is stated that there is positive compensation that can be given to the heart if the dhikr methods are followed and carried out by the owner of the heart. Then how do the views of the commentators explain this correlation in some commentary literature? What is meant by the peace of mind that results from dhikr? This study uses a qualitative research method by analyzing the verses related to the research question and then analyzed with data taken from the opinions of the commentators. The research result states that tarbiyatul qulub through dhikr is to have peace because it makes Allah swt. the main one is nothing but the trembling heart mentioned by the name of Allah Almighty. out of respect for Allah swt. and glorification to Him which has been evident of the majesty of Allah Almighty.  AbstrakManusia diciptakan dengan misi yang jelas. Menurut pakar tafsir, ada tiga misi yang diemban manusia sebagai makhluk Allah swt di muka bumi, misi beribadah, khalifah, berperan memakmurkan bumi. Kemudian ia diberikan beberpa potensi. Salah satu potensi tersebut adalah hati “qalb”.  Pada beberapa ayat al-Qur’an disebutkan terdapat kompensasi positif yang dapat diberikan kepada hati bila cara-cara berdzikir ditempuh dan dilakukan oleh yang pemilik hati. Lalu bagaimana pandangan para mufassir menjelaskan korelasi tersebut dalam beberapa literature kitab tafsir? Apa yang dimaksud dengan ketenteraman hati yang diperoleh dari hasil berdzikir? Penelitian ini menggunakan metode penelitian kualitatif dengan menganalisis ayat-ayat yang berhubungan dengan pertanyaan penelitian dan kemudian dianalisa dengan data-data yang diambil dari pendapat para mufassir. Hasil penelitian menyebutkan bahwa tarbiyatul qulub melalui berdzikir adalah memiliki ketenteraman karena menjadikan Allah swt. yang utama bukan yang lain serta bergemetaran hati yang disebutkan nama Allah swt. karena rasa hormat kepada Allah swt. dan pengagungan kepada-Nya yang telah tampak jelas akan keagungan yang dimiliki Allah swt.